2018
DOI: 10.3389/fchem.2018.00265
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Production of Indole Related Compounds Reveals Their Role in Association Between Duckweeds and Endophytes

Abstract: Duckweed farming can be a sustainable practice for biofuel production, animal feed supplement, and wastewater treatment, although large scale production remains a challenge. Plant growth promoting bacteria (PGPB) have been shown to improve plant health by producing phytohormones such as auxin. While some of the mechanisms for plant growth promotion have been characterized in soil epiphytes, more work is necessary to understand how plants may select for bacterial endophytes that have the ability to provide an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 27 publications
2
96
0
2
Order By: Relevance
“…Obtaining axenic cultures from wild‐collected duckweed is straightforward (Bowker et al., ), and we have ourselves exploited this property to ensure constant environmental conditions in common garden experiments (Barks et al., ). Axenic culture is also useful in the study of plant microbiomes, a topic currently of intense interest (e.g., Gilbert et al., ). Finally, under axenic conditions, duckweed cultures can be maintained at low temperature for up to a year without requiring human intervention, which allows for simple long‐term maintenance of stock cultures.…”
Section: Example Traits Of Duckweeds That Make Them Suitable As Modelmentioning
confidence: 99%
“…Obtaining axenic cultures from wild‐collected duckweed is straightforward (Bowker et al., ), and we have ourselves exploited this property to ensure constant environmental conditions in common garden experiments (Barks et al., ). Axenic culture is also useful in the study of plant microbiomes, a topic currently of intense interest (e.g., Gilbert et al., ). Finally, under axenic conditions, duckweed cultures can be maintained at low temperature for up to a year without requiring human intervention, which allows for simple long‐term maintenance of stock cultures.…”
Section: Example Traits Of Duckweeds That Make Them Suitable As Modelmentioning
confidence: 99%
“…Three candidates met our criteria of being small, polar, and heat and protease resistant molecules (Fig 5): DL-3-Phenyllactic acid (PLA); DL-p-Hydroxyphenyllactic acid (HPLA) and DL-Indole-3-lactic acid (ILA) (S4 Fig). All three are aromatic metabolites derived from amino acid metabolism and are produced by several species of prokaryotes and eukaryotes [61,62]. Testing these three metabolites individually revealed that ILA was the most inhibitory to the inflammasome (Fig 6A), while not affecting TNF-α secretion (Fig 6B).…”
Section: Resultsmentioning
confidence: 99%
“…ILA is an aromatic metabolite derived from the tryptophan pathway. It is produced by a wide variety of organisms and microorganisms, ranging from soil bacteria to humans [61,62]. ILA production in fungi is mostly reported in endophytic and phytopathogenic species, being described as important for plant tissue colonization [79].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, since vitamin B 12 is not measurably present in plant-based foods, individuals adhering to a vegan diet without vitamin B 12 supplementation are at risk of developing vitamin B 12 deficiency with potentially serious and sometimes irreversible consequences [ 3 , 11 ]. Indeed, various types of edible algae have been reported to contain vitamin B 12 [ 4 , 12 ]. However, recent data indicate that pseudo B 12 forms, such as OH-pseudoB 12 , Ado-pseudoB 12 , Me-pseudoB 12 , and CN-pseudoB 12 , which are considered inactive in humans, and might compete with B 12 , are the predominant corrinoids present in the algae [ 4 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, various types of edible algae have been reported to contain vitamin B 12 [ 4 , 12 ]. However, recent data indicate that pseudo B 12 forms, such as OH-pseudoB 12 , Ado-pseudoB 12 , Me-pseudoB 12 , and CN-pseudoB 12 , which are considered inactive in humans, and might compete with B 12 , are the predominant corrinoids present in the algae [ 4 , 12 ].…”
Section: Introductionmentioning
confidence: 99%